Restricted access to health care for asylum-seekers: applying a human rights lens to the argument of resource constraints - Bozorgmehr, Kayvan; Wenner, Judith; Razum, Oliver (European journal of public health, 2017)
Granting health care to vulnerable groups of the population including asylum seekers is often regarded as a ‘benevolent handout (…) by state or third parties to